The Cut of the Clothes of North Caucasian Alans - Orfinskaya, Olga; Arzhantseva, Irina (Archaeological Textiles Review, 2013)
The paper is an attempt to reconstruct the evolution of costume cut through the examination of examples of North Caucasian Alan costume dated to the 8th-13th centuries AD. The analysis indicates that the cut of Alan clothes was based on the Central Asian pattern with a smooth bodice-sleeve line. The cut changed with the gradual transformation from felt to fabric of fixed width and length. Many questions remain controversial yet a new line of inquiry into the cut of excavated sewn clothes is proposed.